Biological activity of SE-10, granulated powder of Sasa senanensis Rehder leaf extract - Sakagami, Hiroshi; Matsuta, Tomohiko; Satoh, Kazue; Ohtsuki, Sumiko; Shimada, Chiyako; Kanamoto, Taisei; Terakubo, Shigemi; Nakashima, Hideki; Morita, Yurika; Ohkubo, Atsuko; Tsuda, Tadashi; Sunaga, Katsuyoshi; et al. (In vivo (Athens), 2012)
We have previously reported that alkaline extract of Sasa senanensis leaves (SE) showed potent anti-HIV, anti-UV and radical scavenging activity. In the present study, we investigated the biological activities of SE-10, a granulated powder of SE supplemented with lactose, lactitol, trehalose and tea extract. Cell viability of mock-infected, HIV-infected, and UV-irradiated cells was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. Scavenging activity of superoxide anion and hydroxyl radicals was determined by electron-spin resonance spectroscopy. Cytochrome P-450 (CYP)3A4 activity was measured by β-hydroxylation of testosterone in human recombinant CYP3A4. SE-10 had slightly higher anti-HIV and anti-UV activities, but slightly lower radical-scavenging and CYP3A4-inhibitory activities, as compared with SE. The present study demonstrates that the biological activities of SE were well preserved during the manufacturing process of SE-10.